Steel drills versus zirconia drills on heat generation at the surgical site of dental implants: A systematic review and meta-analysis - Augusto Alves Bento, Victor [UNESP]; Marcela de Luna Gomes, Jessica [UNESP]; Davi Del Rei Daltro Rosa, Cleber [UNESP]; Pedro Justino de Oliveira Limirio, João [UNESP]; Micheline Dos Santos, Daniela [UNESP]; Coelho Goiato, Marcelo [UNESP]; Piza Pellizzer, Eduardo [UNESP] (Springer Nature, 2024)
Objective: The aim was to evaluate the difference in the heat generated between zirconia (Zr) and steel (SS) drills, during implant site preparation. Material and methods: This systematic review followed the PRISMA methodology criteria and used the JBI Critical Assessment Guidelines for Quasi-Experimental Studies for quality assessment. The electronic search was conducted by using the PubMed/MEDLINE, Embase, and Cochrane Library databases to January 2023. The formulated population, intervention, comparison, outcome (PICO) question was “Do zirconia drills generate less heat than steel drills during implant site preparation?“. The meta-analysis was based on an inverse variance (IV) method. Results: This review included 10 studies in vitro that used zirconia drills compared to steel drills with or without coatings. The meta-analysis indicated a significant difference between Zr drills and SS drills, with a lower bone temperature variation with Zr drills. Conclusions: Despite the limitations of this review, it was concluded that Zr drills had significantly less temperature variation than SS drills.
Keywords: Ceramics; Dental Implants; Hot Temperature; Osteotomy; Stainless Steel